Perceived security, trust, privacy, and continuance intention of e-commerce customer - Desi Novita; Astra Prima Budiarti (Operations Management and Information System Studies, 2022)
This study aims to analyze (1) the effect of perceived security on the continuance intention of Shopee application users, (2) the effect of trust on the continuance intention of Shopee application users, (3) the influence of privacy on the continuance intention of Shopee application users, (4) the effect of satisfaction on the continuance intention of Shopee application users, (5) the effect of perceived security on the continuance intention of Shopee application users through satisfaction, (6) the effect of trust on the continuance intention of Shopee application users through satisfaction, (7) the influence of privacy on the continuance intention of Shopee application users through satisfaction. The sample in this study is Shopee users who have used Shopee more than once. The number of samples in this study was 300 respondents. Data was collected through the distribution of online questionnaires and data processing was carried out through PLS software. The results of this study indicate that continuance intention is positively and significantly influenced by perceived security, trust, and privacy even after being mediated by satisfaction.